2020
DOI: 10.1007/s11270-020-04923-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Road Dust Load and Its Size Distribution—a Comparative Study of a Porous and a Dense Pavement

Abstract: Resuspension of road dust contributes to air quality issues with resulting health impacts. Limited studies imply that porous pavements can initially mitigate PM10 emissions by acting as a dust trap, but the abrasion wear generates road dust and thus accelerates the clogging processes. In addition, knowledge regarding the impact of pavement types on road dust load dynamics is limited. Road traffic noise can be mitigated using porous pavements, but the use of studded tyres increases the abrasion wear of the pave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The mobile data rather suggests a bi-polar relationship between BC and particulate matter (Figure 6b,c): During the winter, BC constituted ~25% of the mass of PM 2.5 , which is consistent with the BC/PM 2.5 ratio associated with fossil fuel burning in a Helsinki street canyon in winter [48]. In spring, BC represented only ~2% of the mass of PM 2.5 in accordance with local road dust, or alternatively long-transport dust, which contributed significantly to particles in the small diameter ranges [42,49].…”
Section: Stationarysupporting
confidence: 75%
“…The mobile data rather suggests a bi-polar relationship between BC and particulate matter (Figure 6b,c): During the winter, BC constituted ~25% of the mass of PM 2.5 , which is consistent with the BC/PM 2.5 ratio associated with fossil fuel burning in a Helsinki street canyon in winter [48]. In spring, BC represented only ~2% of the mass of PM 2.5 in accordance with local road dust, or alternatively long-transport dust, which contributed significantly to particles in the small diameter ranges [42,49].…”
Section: Stationarysupporting
confidence: 75%
“…The effect of dust binding is rather short-lived and dependent on traffic intensity, temperature, and humidity (i.e., parameters affecting how fast the road surface dries). , A study in the warm and dry climate of southern Spain showed that a dust binding agent had very little effect, but street washing with high amounts of water was more effective . Porous pavements have also been shown to conceal dust, thereby contributing to lower resuspension; however, the effect diminishes as the pores become clogged, necessitating effective and regular rinsing . As with all nonexhaust sources, emissions from resuspension are lessened by reduced traffic volumes.…”
Section: Future Scenarios and Mitigation Of Non-exhaust Emissionsmentioning
confidence: 99%
“…For comparison purposes, open-graded (OGP), permeable friction course pavements offer a host of safety and environmental benefits, including improved wet weather skid resistance, reduced splash and spray, reduced light reflection, reduced tire and pavement noise, improved pavement smoothness, reduced contribution to urban heat island effect, and reduced pollutant loadings in stormwater runoff [19]. However, they perform worse than DGP in winter, as they freeze faster and longer, need more deicing agents, their pores can store and retain snow and dust, and their aggregate structure makes them particularly susceptible to degradation, especially by studded tires [19,26,54]. Last, the short-term road management actions of dust binding provide no auxiliary benefits other than reducing particulate matter episodes.…”
Section: Mitigation Strategies For Sustainable Citiesmentioning
confidence: 99%